2018
DOI: 10.2147/idr.s167518
|View full text |Cite
|
Sign up to set email alerts
|

Malaria parasite clearance from patients following artemisinin-based combination therapy in Côte d’Ivoire

Abstract: IntroductionParasite clearance is useful to detect artemisinin resistance. The aim of this study was to investigate parasite clearance in patients treated with artesunate + amodiaquine (AS + AQ) and artemether + lumefantrine (AL): the two artemisinin-based combination therapies (ACTs) recommended in the first-line treatment of uncomplicated malaria in Côte d’Ivoire.MethodsThis study was conducted in Bouaké, Côte d’Ivoire, from April to June 2016. Patients aged at least 6 months with uncomplicated malaria and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…The study has shown that day 3 parasitaemia, which is an indicator of artemisinin or partial resistance [ 22 ] has remained less than 1% with no statistically significant increase in proportions between 2005 (0.2%) and 2018 (0.6%). This finding suggests that artemisinin remains a viable component of combination therapy in the management of uncomplicated malaria in Ghana, and compares well with findings in the sub-region [ 23 25 ].…”
Section: Discussionsupporting
confidence: 81%
“…The study has shown that day 3 parasitaemia, which is an indicator of artemisinin or partial resistance [ 22 ] has remained less than 1% with no statistically significant increase in proportions between 2005 (0.2%) and 2018 (0.6%). This finding suggests that artemisinin remains a viable component of combination therapy in the management of uncomplicated malaria in Ghana, and compares well with findings in the sub-region [ 23 25 ].…”
Section: Discussionsupporting
confidence: 81%
“…is is consistent with other studies that studied malaria determinants in Zambia [27,28]. Antimalarial drugs such as artemisinin combination therapies (ACTs) are known to clear parasiteamia within few days of commencement of effective treatment; one study in Cote d'Ivoire found a median parasite clearance of 30 hrs [29]. Another study recommended a day-three blood slide as a good predictor of treatment success [30].…”
Section: Discussionsupporting
confidence: 80%
“…The study was carried out during a clinical trial that aimed to assess the in vivo efficacy of artemisinin-based anti-malarial combination therapies. Details of the study, clinical procedures, and drug administration are described elsewhere [ 45 ]. Briefly, patients ( n = 120, age > 6 months) with uncomplicated malaria and monospecific P. falciparum infestation confirmed by microscopy (parasite density between 2000 and 200,000 asexual parasites/μL of blood), axillary temperature of ≥37.5 °C, or a history of fever over the past 24 h, with body weight ≥5 kg, and who were able to take oral medications and follow study procedures were included in the study.…”
Section: Methodsmentioning
confidence: 99%